Degradation of chlorpyrifos and inactivation of Escherichia coli O157:H7 and Aspergillus niger on apples using an advanced oxidation process. (March 2020) - Ho, J.; Prosser, R.; Hasani, M.; Chen, H.; Skanes, B.; Lubitz, W.D.; Warriner, K.
Abstract: Chlorpyrifos is a widely used insecticide in apple production but there are concerns that residues ingested by consumers can lead to chronic neurological conditions. In the following, a method based on Advanced Oxidation Process (AOP) was validated for the degradation of chlorpyrifos on apples and inactivating Escherichia coli O157:H7, along with Aspergillus niger spores. AOP is a process that generates free-radicals from the UV-C (at 254 nm) mediated degradation of hydrogen peroxide thereby leading to highly oxidative species. By using Response Surface Methodology (RSM) it was found that the degradation of chlorpyrifos was primarily dependent on UV-C dose and synergistically enhanced by applying the hydrogen peroxide at temperatures up to 66 °C. However, the degradation of chlorpyrifos was independent on the hydrogen peroxide concentration up to 6% v/v. Maximal degradation of chlorpyrifos on apples was achieved through an AOP treatment applying 68.4 kJ/m 2 UV dose and 1.22% v/v H2 O2 at 66 °C that resulted in 118 μg degradation (representing 59% of the original level) of the pesticide with <20 ppb accumulation of the degradative photoproduct, CPY-O. The same treatment supported a >6.6 log CFU reduction in E. coli O157:H7 and >4.7 log CFU reduction of A. niger spores. Applying UV alone in the case of E. coli O157:H7 or hydrogen peroxide alone against A. niger spores supported a lower level of lethality compared to AOP. In conclusion, the study has demonstrated that an AOP based process can support the degradation of chlorpyrifos and address microbiological hazards associated with apples. Highlights: An Advanced Oxidation Process was optimized for degrading chlopyrifos on apples. UV-C contributed to degradation reaction to a greater extent than hydrogen peroxide. An AOP process comprised of 69 kJ/m2 and 1, 22% hydrogen peroxide supported 59% chlorpyrifos degradation. Optimized treatment decreased E. coli O157 and Aspergillus niger spores to below the limit of detection. The process developed can be applied to address chemical and microbial hazards associated with apples.